ANALISIS HUBUNGAN FUNDAMENTAL DAN HARGA SAHAM DI INDEKS LQ45: PERAN INFLASI SEBAGAI VARIABEL MODERASI - Prawitasari, Putu Putri; Krisna Wiguna, Putu; Istri Agung Maheswari, Anak Agung; Arniti, Ni Ketut (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to examine the effect of earnings per share (EPS) and return on assets (ROA) on stock prices with inflation as a moderating variable in LQ 45 mining sector companies for the 2023 period.The population in this study is 10 mining sector companies listed in the LQ 45 composite stock index in 2023. The sampling technique uses the purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses multiple linear regression analysis with SPSS. The results of this study provide empirical evidence that the EPS independence variable has a positive effect on the stock price while ROA has a negative effect on the stock price, and inflation is unable to moderate EPS and ROA on the stock price